Can the toxicity of polyethylene microplastics and engineered nanoclays on flatfish (Solea senegalensis) be influenced by the presence of each other? - Santana, Lígia M.B.M. [UNESP]; Rodrigues, Andreia C.M.; Campos, Diana; Kaczerewska, Olga; Figueiredo, Joana; Silva, Sara; Sousa, Isabel; Maia, Frederico; Tedim, João; Abessa, Denis M.S. [UNESP]; Pousão-Ferreira, Pedro; Candeias-Mendes, Ana; et al. (Elsevier, 2022)
Microplastics and nanomaterials are applied in a myriad of commercial and industrial applications. When leaked to natural environments, such small particles might threaten living organisms' health, particularly when considering their potential combination that remains poorly investigated. This study investigated the physiological and biochemical effects of polyethylene (PE; 64-125 μm in size, 0.1, 1.0, and 10.0 mg·L−1) single and combined with an engineered nanomaterial applied in antifouling coatings, the copper-aluminium layered double hydroxides (Cu-Al LDH; 0.33, 1.0, and 3.33 mg·L−1) in the flatfish Solea senegalensis larvae (8 dph) after 3 h exposure, in a full factorial design. Particles ingestion, histopathology, and biochemical biomarkers were assessed. Fish larvae presented <1 PE particles in their gut, independently of their concentration in the medium. The histological health index showed minimal pathological alterations at PE combined exposure, with a higher value observed at 1 mg LDH·L−1 × 0.1 mg PE·L−1. Gut deformity and increased antioxidant defences (catalase), neurotransmission (acetylcholinesterase), and aerobic energy production (electron transport system) were observed at PE ≥ 1.0 mg·L−1. No oxidative damage (lipid peroxidation) or alterations in the detoxification capacity (glutathione-S-transferase) was observed on single and combined exposures. PE, combined or not with Cu-Al LDH, does not seem to compromise larvae's homeostasis considering levels reported so far in the marine and aquaculture environments. However, harsh effects are expected with MP contamination rise, as projections suggest.
Keywords: Biochemical biomarkers; Co-exposure; Cu-Al layered double hydroxides (Cu-Al LDH); Fish embryotoxicity; Histopathology; Nanomaterials; Plastic pollution